Effects of exposure in single and multiple contexts on fear renewal: The moderating role of threat-specific and nonspecific emotionality. (March 2017) - Olatunji, Bunmi O.; Tomarken, Andrew; Wentworth, Brian; Fritzsche, Laura
Abstract: Background and objectives: The current study examines effects of exposure in multiple contexts on fear reduction and renewal and the moderating effect of baseline threat-specific and nonspecific emotionality. Methods: Snake-fearful participants received a negative or neutral emotion induction and were randomized to video exposure to a snake in a single context, multiple context, or a no exposure control group. Results: Anxiety in response to video presentations of a snake was significantly reduced in the two exposure groups compared to the control group, especially among those with heightened baseline threat-specific emotionality as indicated by snake anxiety ratings at baseline. Although the two exposure groups did not differ in responding when confronted with a novel snake, both exposure groups reported significantly lower snake anxiety and arousal than the control group. Subsequent analysis did show that compared to controls, the single context group demonstrated greater increase in anxiety and arousal from post-exposure to exposure to the novel snake among those with heightened snake anxiety at baseline. Furthermore, the multiple context group was less avoidant and less fearful than the single context group on a post-exposure behavioral test. Limitations: The study used an analogue exposure paradigm with an analogue sample and findings may not be generalizable to a clinical population. Conclusions: These findings suggest that baseline threat-specific emotionality influences fear reduction and renewal. The benefits of exposure in multiple contexts are discussed in relation to a distinct pattern of symptom change that is in line with an inhibitory learning approach. Highlights: Exposure reduced snake anxiety among those with higher baseline anxiety. Single context exposure resulted in an increase in anxiety to novel exposure. Exposure in multiple context resulted in less behavioral avoidance.